2012
DOI: 10.1017/s1368980012004302
|View full text |Cite
|
Sign up to set email alerts
|

Public health benefits and risks of fish consumption: current scientific evidence v. media coverage

Abstract: Objective: To evaluate if and how the current degree of scientific uncertainty about the safety of fish consumption is incorporated at the media level. Design: We used a dedicated software (TalTac R ) to investigate the content of 169 news articles related to 'mercury and fish consumption' that appeared from 1990 to 2010 in the two Italian broadsheets with the highest circulation figures, in order to identify journalistic frames used in the coverage of benefits v. risks associated with fish consumption. Hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Regarding fatty acids, although obviously the recommendation is to increase the consumption of seafood, the availability of these products is low, of high cost and concerns have arisen regarding contaminants [ 57 ]. The development of new food alternatives is essential to meet the daily recommendation of n -3 PUFA, specifically DHA, particularly in pregnant and lactating women.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding fatty acids, although obviously the recommendation is to increase the consumption of seafood, the availability of these products is low, of high cost and concerns have arisen regarding contaminants [ 57 ]. The development of new food alternatives is essential to meet the daily recommendation of n -3 PUFA, specifically DHA, particularly in pregnant and lactating women.…”
Section: Discussionmentioning
confidence: 99%
“…Media coverage undoubtedly plays an important role in affecting public opinion about scientific issues, such as nuclear power (Gamson and Modigliani, 1989), technological and environmental hazards (Wiegman et al, 1989), biotechnology (Nisbet and Lewenstein, 2002), nanotechnology (Gorss et al, 2005; Lewenstein et al, 2007), nutrition, and public health (Pasquaré et al, 2013). Several studies have shown that the media do so by using certain, and often stereotypical, frames of reference (Candela, 2013; Castells, 2009; Entman, 1993; Gavrila, 2012; Gilliam and Bales, 2001; Guizzardi, 2002; Neuman et al, 1992; Nisbet and Lewenstein, 2002).…”
Section: Science Representation In the News Mediamentioning
confidence: 99%
“…5 However, the information available to the public on the health effects of fish consumption is insufficient, does not usually differentiate among fish types, and may be influenced by the media outlet where it is presented. 6 Within this context, there is still uncertainty about the metabolic effects of usual fish consumption. Synthesizing and clarifying the existing evidence in this regard may serve to guide public health and food policy, and provide the public with upto-date information in this regard.…”
Section: Introductionmentioning
confidence: 99%
“… 5 However, the information available to the public on the health effects of fish consumption is insufficient, does not usually differentiate among fish types, and may be influenced by the media outlet where it is presented. 6 …”
Section: Introductionmentioning
confidence: 99%